Dynamic R&D choice and the impact of the firm's financial strength - Bettina Peters; Mark J. Roberts; Van Anh Vuong (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This article investigates how a firm's financial strength affcts its dynamic decision to invest in R&D. We estimate a dynamic model of R&D choice using data for German firms in high-tech manufacturing industries. The model incorporates a measure of the firm's financial strength, derived from its credit rating, which is shown to lead to substantial differences in estimates of the costs and expected long-run benefits from R&D investment. Financially strong firms have a higher probability of generating innovations from their R&D investment, and the innovations have a larger impact on productivity and profits. Averaging across all firms, the long run benefit of investing in R&D equals 6.6 percent of firm value. It ranges from 11.6 percent for firms in a strong financial position to 2.3 percent for firms in a weaker financial position.
Keywords: O31; O32; G30; 330; R&D choice; Financial strength; Innovation; Productivity; Dynamic structural model